RELASI ANTARA BISNIS DAN HAK ASASI MANUSIA DITINJAU DARI JOHN RUGGIE PRINCIPLES - Cholidah, Cholidah (Al-Qisth Law Review, 2017)
Corporations as the subject of law in its business activity has great potential to commit human rights violations either committed as the act of the Corporations with the pattern of human rights violation conducted by Direct Complicity that is human rights violation with direct involvement, Beneficial Complicity where company take direct benefit from human rights violation which others do. Silent Complicity as a form of corporate failure to stop or even do something when there are laws or laws that discriminate against a group in society. Violations committed by international and national corporations do not yet have a firm legal instrument that governs the accountability of the Corporations against human rights violations until July 6, 2011 based on United Nations Guiding Principles on Business and Human Rights. The relationship between business and human rights is conceptualized in the three pillars of the framework. The first pillar, stipulates that the state has an obligation to prevent, investigate, compensate and punish the violations of human rights committed by private actors. The second pillar, provides that corporations have a responsibility to respect human rights. The third pillar stipulates that the government should provide recovery access for victims of human rights violations.